An integrated framework to support sustainable electricity planning - Ferreira, Paula Varandas (2012)
The changes in the electricity sector along with the need for sustainable development required traditional electricity planning to expand beyond pure financial analysis and even beyond direct environmental impact analysis. The electricity planner has now the task of designing electricity strategies for the future with the view of enhancing the financial performance of the sector while simultaneously addressing environmental and social concerns. However, the integration of the relevant dimensions of sustainable electricity planning poses important challenges to researchers. In addition, to properly deal with the increasing use of renewable energy sources of variable output, traditional optimisation models must be able to integrate the short term operational planning and dispatching process with the long range planning models. This paper proposes a new framework to sustainable electricity planning, based on optimisation models for electricity power planning combined with participatory methodologies for addressing the social dimension of the problem. The effective implementation of this framework is demonstrated for a real case study based on the Portuguese electricity system. The research started from the presentation of electricity generation scenarios for 2020 drawn from a mixed integer linear optimization model. These scenarios were then characterized under different social, economic and environmental impacts, and evaluated according to a multicriteria procedure based on experts’ inputs.